2017
DOI: 10.22271/ortho.2017.v3.i3a.09
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of functional outcome in intraraticular lower end of humerus fracture treated with dual plating

Abstract: Context: It has been suggested that, with appropriate instruction and practice by the individual and normalization of the reaching distances, the SEBT can be used to provide objective measures to differentiate deficits and improvements in dynamic postural-control related to lower extremity injury and induced fatigue, and it has the potential to predict lower extremity injury. However, literature on its role in assessing proprioception deficits in anterior cruciate ligament deficient knees is limited. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Due to the characteristic intra articular involvement, displacement, and poor control of fracture fragments with closed treatment, we typically treat these fractures operatively. The goal of treatment is restoring painless and functional elbow in a fractured distal humerus which requires anatomical reconstruction and stable fixation [3] . In our study most of distal humerus fractures are intra articular and involve both the medial and lateral columns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the characteristic intra articular involvement, displacement, and poor control of fracture fragments with closed treatment, we typically treat these fractures operatively. The goal of treatment is restoring painless and functional elbow in a fractured distal humerus which requires anatomical reconstruction and stable fixation [3] . In our study most of distal humerus fractures are intra articular and involve both the medial and lateral columns.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-contoured column specific locking plates useful in osteoporotic bone fixation [3] . Several variables are important in successful management of these fractures: restoration of articular congruity, secure bony fixation, achievement of bony healing, maintenance of a functional range of motion, and avoidance of complications such as hypertrophic ossification and ulnar neuropathy [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riyaz sheik et al [16] , Shao-hua Li et al (2011) [18] and Imran mang et al (2014) [19] in their studies found that fractures occured more likely due to high velocity RTA which is in accordance with our study. Kiran GU et al (2017) [20] in their study found that average time of fracture union was achieved in 16.4 weeks in 20 patients, Muzaffar N et al (2014) [21] in their study found that fracture united in 25 patients by 10-16 weeks with an average time of 12.56 weeks. These are consistent with with our findings; wherein fracture union was achieved in an average time of 15 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…The decision of operative treatment is based on many factors, including fracture types, intra-articular involvement, fragments displacement, bone quality, joint stability and soft tissue condition and coverage 10 . The aims of treatment in these fractures are restoring painless and functional elbow which is achieved by anatomical reconstruction and stable fixation 11 . Pre-operatively patients must understand outcome expectation and importance of rehabilitation.…”
Section: Poor 1 5%mentioning
confidence: 99%